Correlation between serum apolipoprotein A1 and serum uric acid level in patients with hyperuricemia - Yuan Wang; Zongwei Wang; Xin Li; Baoyu Zhang (Wolters Kluwer Medknow Publications, 2019)
Objective: Patients with hyperuricemia is often associated with hyperlipidemia. Therefore, the relationship between serum apolipoprotein A1 (Apo-A1) and serum uric acid (UA) level was studied. Methods: Seventy-three patients with gout, 43 patients with hyperuricemia, and 70 healthy controls were enrolled in the study. The liver and kidney function, blood glucose, blood lipid and other biochemical indicators were detected, and Apo-A1 content was detected by enzyme-linked immunosorbent assay. Results: 73 patients with gout, 43 patients with hyperuricemia, and 70 healthy controls were included in the study. None of the patients had diabetes, hypertension, coronary heart disease, or other chronic diseases. There was no difference in blood lipids among the three groups. The lower expressed Apo-A1 was validated in the hyperuricemia group and gout group (P < 0.001). Among all patients, Apo-A1 levels were negatively correlated with plasma UA level (R2 = −0.4925, P < 0.0001). Conclusion: It was confirmed that Apo-A1 was related to the change of plasma UA level to some extent.